Ecological methods: with particular reference to the study of insect population - Southwood, T. R. E (Chapman and Hall / London, 1978)
The contents of information is :Introduction to the Study of Animal Populations., The Sampling Programmed and the Measurement and Description of Dispersion., Absolute Population Estimates Using Capture–Recapture Experiments., Absolute Population Estimates by Sampling a Unit of Habitat: Air, Plants, Plant Products, and Vertebrate Hosts, Absolute Population Estimates by Sampling a Unit of Aquatic Habitat, Absolute Population Estimates by Sampling a Unit of Soil or Litter Habitat: Extraction Techniques., Relative Methods of Population Measurement and the Derivation of Absolute Estimates, Indices: the Use of Signs, Products, and Effects, Wildlife Population Estimates by Census and Distance-measuring Techniques, Observational and Experimental Methods for the Estimation of Natality, Mortality, and Dispersal., The Construction, Description, and Analysis of Age-specific Life-tables., Age-grouping, Time-specific Life-tables, and Predictive Population Models, Species Richness, Diversity, and Packing., The Estimation of Productivity and the Construction of Energy Budgets, Large Scale Spatial and Temporal Studies and the Classification of Habitats.